STABLE EXPRESSIONS WITH VISUAL PERCEPTION VERBS IN RUSSIAN - Abdusattarova , Parvina (Science technology&Digital finance, 2024)
Paying attention to the functioning of visual perception in the linguistic picture of the world through the prism of the object of visual perception and the evaluativeness depending on it, it should be said that the subject of visual perception sometimes chooses an object mistakenly. It turns out that the linguistic picture of the world captures priority objects that are more useful to look at than others. On the other hand, a person pays attention to what he particularly likes, to what interests him ‒ then he perceives this object intensely. What the subject of visual perception has not yet perceived with the help of vision is considered unusual, exceptional.